Restorative Justice: Insights and Stories from My Journey - Zehr, Howard (Walnut Street Books, 2023)
Front Cover -- Title Page -- Copyright -- Contents -- Who is Howard Zehr? -- Beginning the Journey -- Part 1: What Exactly Is Restorative Justice? -- Chapter 1: Restorative Justice-The Promise, the Challenge -- A conversation with Katia Cecilia Ornelas-Nuñez -- Chapter 2: Journey to Belonging: What "victims" and "offenders" have in common -- Chapter 3: Good Intentions Aren't Enough -- Chapter 4: The Promise and the Challenge of Restorative Justice for Victims (with Mary Achilles) -- Chapter 5: Justice as Art, Art as Justice -- Part 2: How I Got Here, Personally -- Chapter 6: How I Got Here -- A conversation with Bruna Pali -- Chapter 7: Restorative Justice and the Gandhian Tradition -- Chapter 8: Looking Back on My Career and the Field: Reflections upon receiving an award -- Part 3: Photography, Art-and Radio-at the Healing Edge -- Chapter 9: The Meaning of Life-Working at the Healing Edge -- Chapter 10: When a Parent Is in Prison -- Chapter 11: Amateur Radio for Boys and Geezers -- Part 4: Restorative Justice: A Vision to Guide and Sustain Us in All of Life -- Chapter 12: Beyond Crime: A Vision to Guide and Sustain Us -- Chapter 13: Ten Ways to Live Restoratively -- Chapter 14: Do We Need More Jails? -- Chapter 15: New Zealand's Unique Approach to Youth Offending -- Chapter 16: Education on the Healing Edge? -- Thinking back. . . Imagining ahead -- To Howard Zehr -- Acknowledgments -- Text Credits -- Photography Credits -- About the Author.